Redescription of Pethia melanomaculata (Teleostei: Cyprinidae) from Sri Lanka - Batuwita, Sudesh; Maduwage, Kalana; Sudasinghe, Hiranya (Zootaxa, 2015)
The name Pethia melanomaculata (Deraniyagala) is available for the Sri Lankan fish previously referred to P. ticto, being distinguished from its Indian congeners by the combination of the following characters; having ½4/1/3½ scales in transverse line on body; body depth 32.4–41.5% of standard length (SL); head length (HL) 26.1–29.2% of SL; snout length 25.3–35.6% of HL; eye diameter 24.4–31.9% of HL; a small black humeral spot on lateral-line scales 3 or 4; a black spot on caudal peduncle, on scales 16–18 of the lateral line series; 3 unbranched dorsal-fin rays, the last one strongly serrated, with 8–11 serrae.